POTENSI PENDUKUNG PELAKSANAAN PROGRAM INDONESIA PINTAR: STUDI KASUS DI KECAMATAN BABAKAN KABUPATEN CIREBON - Meiynana; Sari Viciawati Machdum (Balitbang Kemendikbud, 2020)
The study aims to determine the potential support for the implementation of PIP policies in an effort to improve access to education for school-age children who come from underprivileged families. This research is a case study in Babakan subdistrict which based on preliminary observations shows an indication of successful PIP implementation. This research uses a descriptive qualitative approach. The data is collected through document review by analyzing the PIP report data and in-depth interviews with relevant stakeholders. The results show that the successful implementation of PIP was supported by four interrelated aspects, including good communication and coordination between the stakeholders involved in tiered, adequate resources, and a good bureaucracy based on their roles and functions. It is hoped that the research results can inspire and motivate other regions to implement PIP.